Resistance Against Traditional Gender Roles by Sansa Stark - Aziimatussaadah, Angelina (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
Abstract This research explores Judith Butler's concept of gender roles in the book "Gender Trouble" and James Scott's theory of resistance. Butler's concept examines gender, while Scott's theory is a theory of resistance in the dividual or group forms of closed and open ways of resistance. By using the character Sansa Stark in the Game of Thrones series, this research analyzes Sansa Stark's resistance to traditional gender roles in Season 6 and also how it impacts her life. This analysis shows how Game of Thrones breaks traditional gender norms and patriarchal structures by presenting strong female characters such as Sansa Stark as one of the strong female characters in the male fiction series Game of Thrones. Keywords: Resistance, Gender roles, Traditional